Clinical, Hematologic, and Molecular Findings in Naturally Occurring Babesia canis vogeli in Egyptian Dogs. (11th February 2014) - Salem, N. Y.; Farag, H. S.
Abstract : Background . Canine babesiosis is a clinically important hemoprotozoan parasite affecting dogs. The goal of this present study was to determine the clinical symptoms and to establish its hematological and microscopic detection and compare it with the PCR findings attained from dogs infected with Babesia canis vogeli . Methodology/Principal Findings . 13-PCR confirmed Babesia-infected dogs were examined; seminested PCR was used to discover the precise type of Babesia and Babesia canis vogeli was the only subspecies detected. The most consistent clinical signs were elevated rectal temperature and a pale mucous membrane. Thrombocytopenia, monocytosis, and lymphocytosis, along with a significant reduction in red cell parameters, were the most commonly recorded hematologic alterations. Microscopic examination revealed the presence of typical large merozoites and trophozoites of B. canis in the ratio 76.92%. Conclusions/Significance . The presumptive diagnosis of canine babesiosis should be based on a fever and anemia, while thrombocytopenia is considered the hallmark of the disease; microscopic examination may not be very revealing in the detection at low parasitemia, but it remains the most rapid confirmatory method. Seminested PCR turned out to be a sensitive and accurate method for diagnosis; during the process of differentiation between Babesia subspecies, only B. canis subsp. vogeli was detected.